MENDUKUNG STRATEGI PROMOSI TERINTEGRASI MOBILE APPLICATION “OTOCARE” PT. ASURANSI ASTRA - Henni Gusfa (MediaKom : Jurnal Ilmiah Komunikasi, 2017)
In support of mobile application "Otocare", PT. Astra Insurance requires an integrated promotional strategy, with the movement of all components owned by the company, designing it, and also apply it in the strictly dynamics of competence Insurance company in Indonesia. This research has purpose to know and analyze from various application of promotion strategy that support the implementation of Mobile application "Otocare", so that will be found any obstacles in the implementation, and given the solution to limit the barrier, and improve service to Customer PT. Astra Insurance. This study uses the theory of Integrated Marketing Communication (IMC) Belch, using constructivist paradigm, with qualitative research design. Methods were performed with in-depth interviews, with a single case study approach, which placed the case as the focus of the study. From the data obtained then in though by testing the validity of data with trustworthtiness, namely authenticity, and triangulation of data. The results in this study are an analysis of various promotional channels conducted in support of mobile application service "otocare" using SOSTAC model. From all analyzes and results obtained can be concluded that the implementation of promotional strategies to support mobile application "Otocare" This can improve services for customers Garda Oto, PT. Astra Insurance.Keywords : Communication, Promotion Strategy, Mobile application, IMC, SOSTAC